2018
DOI: 10.1161/jaha.117.007944
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Heart Failure Admissions Under Observation Versus Short Inpatient Stay

Abstract: BackgroundPatients with heart failure (HF) are admitted either under observation (OBS) or inpatient stays; however, there is little data on whether this designation reflects the clinical status of a patient, with significant logistical and financial implications. We sought to compare the outcomes of patients with HF admitted OBS versus inpatient stay (≤2 days; INPT).Methods and ResultsFrom January 1, 2008 to September 30, 2015, our multisite health system saw 21 339 unique patients totaling 52 493 hospital adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…However, at 90 days, both the readmission and mortality rates were similar between the 2 groups, suggesting that patients presenting with chest pain designated to observation status may portend a better prognosis than the short inpatient stay group, at least in the short-term. This is different from the results of the current study by Masri et al, 12 raising the question of whether it may be easier to prognosticate patients with chest pain and predetermine hospitalization status, compared with those with HF. Bellolio et al conducted a similar study, whereby the investigators compared observation status with short inpatient stay (<48 hours) in patients presenting with chest pain.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…However, at 90 days, both the readmission and mortality rates were similar between the 2 groups, suggesting that patients presenting with chest pain designated to observation status may portend a better prognosis than the short inpatient stay group, at least in the short-term. This is different from the results of the current study by Masri et al, 12 raising the question of whether it may be easier to prognosticate patients with chest pain and predetermine hospitalization status, compared with those with HF. Bellolio et al conducted a similar study, whereby the investigators compared observation status with short inpatient stay (<48 hours) in patients presenting with chest pain.…”
contrasting
confidence: 99%
“…[8][9][10][11] In this context, the results of the interesting study by Masri et al, published in this issue of Journal of the American Heart Association (JAHA), add to the debate. 12 The investigators compared outcomes of 11 355 HF admissions under observation (n=2648) with short inpatient stay (ie, <2 midnights; n=8709) from January 2008 to September 2015 within a large healthcare system of 8 hospitals. They examined differences between the 2 groups in baseline characteristics and outcomes of readmission (including both inpatient and observation stays) at 1, 3, and 12 months and mortality at 1 year after discharge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such pathways may be intended to increase patient-centered care, but recent research suggests potential for increased morbidity and mortality. 45,46 For instance, a 2017 study by Sax et al 45 found that 1 in 3 patients with CHF discharged from the ED had a repeat ED visit, hospitalization, or death within 30 days after ED discharge. More research should examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…At a same-day access HF clinic launched by Duke University Hospital, a 10% reduction in 30-day readmissions was observed out of over 3,000 visits over the course of 3 years 26. On the other hand, a retrospective multicenter study found readmission rates higher for HF treatment in observation units compared to inpatient hospital treatment, suggesting the need for improvements in the process of determining which worsening HF patients are most appropriate for OP treatment 27…”
Section: Discussionmentioning
confidence: 99%